Venous thromboembolism in medical outpatients – a cross-sectional survey of risk assessment and prophylaxis - Lawall, Holger; Matthiessen, Andreas; Hohmann, Volker; Bramlage, Peter; Haas, Sylvia; Schellong, Sebastian (Thrombosis and Haemostasis, 2011)
The degree of thromboprophylaxis in medical outpatients is low despite a substantial risk for venous thromboembolism (VTE). This may be attributable to difficulties in assessing risk. Assessment tools like the Haas’ scorecard aid in determining the need for thromboprophylaxis. We aimed at evaluating how the use of this tool may aid physicians in appropriately using anticoagulants. This was an epidemiological, cross-sectional survey of acute medically ill patients with limited mobility treated by general practitioners and internists. Risk assessment for VTE by the treating physician was compared to calculated risk. Of 8,123 patients evaluated between August 2006 and April 2008, 7,271 fulfilled the in- and exclusion criteria. Mean age was 69.4 ± 13.6 years, and 45.2% were male. Of these 82.8% were high risk based on their acute medical condition, 37.9% based on their underlying chronic condition. Immobilisation, heart failure, pneumonia, age, obesity, and major varicosis were the most frequently encountered risk factors. The agreement between the Haas’ scorecard and physician indicated risk was high. At least 94.1% of patients with high risk received adequate anticoagulation mostly as low molecular weight heparins for a mean duration of 15.1 ± 30.5 days. There is a substantial risk for VTE in medical out-patients. Using a simple structured scorecard resulted in an overall appropriate risk assessment and high degree of anticoagulation. The scorecard may provide a tool to improve the overall awareness for VTE risk in medical outpatients, substantially improving the degree of prophylaxis in a patient population with largely underestimated risk.
Keywords: Venous thromboembolism; dispositional risk; expositional risk; enoxaparin; scorecard; risk assessment